Exploring the role of the lecturer in developing self-regulated learning skills in students - Wilmot, Lanelle Jean (My University, 2015)
This paper reports the findings of an action research intervention designed to explore the student experiences of a lecturer’s role-modelling specific cognitive self-regulated learning (SRL) skills on third year Financial Accounting students’ motivation and strategies for learning. The intervention involved a series of enrichment tutorials with a pilot group of Financial Accounting III students at the University of the Witwatersrand, Johannesburg. A mixed methods research approach was used in the study. Qualitative data was collected in the form of verbal and written feedback from group participants and the lecturer’s research diary. Quantitative data was gathered by means of the Motivated Strategies for Learning Questionnaire (MSLQ), which was used to measure the students’ motivations and strategies for learning before and after the intervention. The intervention involved a lecturer role-modelling specific learning skills through the use of active learning activities. The skills role-modelled focussed on the following MSLQ learning strategies: rehearsal, organisation, elaboration, critical thinking, meta-cognitive self-regulation, and time and study environment management. Results suggest that role-modelling in an active learning environment does help students to implement SRL skills and experience the value of using the skills. Students reported making changes to their learning approaches to Financial Accounting III as a result of the intervention. Additionally the study identified the need for students to be taught the academic discourse of financial accounting within the course content.
Thesis (M. Com. (Accountancy))--University of the Witwatersrand, Faculty of Commerce, Law and Management, School of Accountancy, 2014.
Keywords: Self-regulated learning; Accountancy education; Lecturer role-modelling; Action research; Cognitive learning strategies; Active learning; Academic discourse